Rhodiola rosea Reduces Intercellular Signaling in Campylobacter jejuni - Ajda Kunčič; Franz Bucar; Sonja Smole Možina (MDPI AG, 2022)
Campylobacter jejuni is a major foodborne pathogen and the leading cause of bacterial gastroenteritis, i.e., campylobacteriosis. Besides searching for novel antimicrobials, identification of new targets for their action is becoming increasingly important. Rhodiola rosea has long been used in traditional medicine. Ethanolic extracts from the roots and rhizomes of the plant contain a wide range of bioactive compounds with various pharmacological activities. In this study, cultivated plant materials have been used, i.e., "Mattmark" and "Rosavine". Through optimized protocols, we obtained fractions of the initial ethanolic extracts rich in most important bioactive compounds from R. rosea, including salidroside, rosavins, proanthocyanidins (PACs), and flavonoids. The antimicrobial activity in relation to the chemical composition of the extracts and their fractions was studied with an emphasis on C. jejuni AI-2-mediated intercellular signaling. At concentration 15.625 mg/L, bioluminescence reduction rates varied from 27% to 72%, and the membrane remained intact. Fractions rich in PACs had the strongest antimicrobial effect against C. jejuni, with the lowest minimal inhibitory concentrations (MICs) (M F3 40%: 62.5 mg/L; R F3 40%: 250 mg/L) and the highest intercellular signaling reduction rates (M F3 40%: 72%; R F3 40%: 65%). On the other hand, fractions without PACs were less effective (MICs: M F5 PVP: 250 mg/L; R F5 PVP: 1000 mg/L and bioluminescence reduction rates: M F5 PVP: 27%; R F5 PVP: 43%). Additionally, fractions rich in flavonoids had strong antimicrobial activity (MICs: M F4 70%: 125 mg/L; R F4 70%: 250 mg/L and bioluminescence reduction rates: M F4 70%: 68%; R F4 70%: 50%). We conclude that PACs and flavonoids are crucial compound groups responsible for the antimicrobial activity of R. rosea roots and rhizomes in C. jejuni.